How to share complex data and knowledge: Application in Bio-Imaging. Issue 12 (2016) - Pham, Cong Cuong; Matta, Nada; Durupt, Alexandre; Eynard, Benoit; Allanic, Marianne; Ducellier, Guillaume; Joliot, Marc; Boutinaud, Philippe
Abstract: Information Systems, used to share information, lead to the growth of heterogeneous data and then the dependencies between them. Thus, the links and dependencies among heterogeneous and distributed data are more and more complex during daily activities of users (engineers, researchers, etc.). Ontology is currently used to enhance the knowledge sharing and the data integration in many information systems. Our contribution is to propose a methodology to facilitate the exploitation (interrogation and sharing) of data in an organization using Bio-Imaging ontology.